The ethanolic extract of Juglans sinensis leaves and twigs attenuates CCl(4)-induced hepatic oxidative stress in rats - Yang, Heejung (Pharmacogn Mag, 2015)
BACKGROUND: The nuts of Juglans sinensis Dode, walnut tree, are rich in unsaturated fatty acids and bioactive compounds with antioxidant activity on liver damages. However, hepatoprotective activity of the leaves and twigs of J. sinensis have not intensively studied yet. OBJECTIVE: Hepatoprotective activity of the refined ethanolic extract of J. sinensis (JSE3) was evaluated using carbon tetrachloride (CCl(4))-intoxicated rats. MATERIALS AND METHODS: Hepatotoxicity was induced in Sprague Dawley rats by intraperitoneal injection of CCl(4) for 6 weeks in the presence or absence of JSE3 (100 and 200 mg/kg body weight). The hepatoprotective activity of JSE3 was assessed by biochemical parameters including plasma aspartate aminotransferase (AST), alanine aminotransferase (ALT), and antioxidant enzymes, such as superoxide dismutase (SOD), glutathione reductase, glutathione peroxide, reduced glutathione and oxidized glutathione, along with histopathological studies on hepatic tissue. RESULTS: JSE3 significantly decreased the elevated levels of AST and ALT and restored the reduced levels of antioxidant enzymes. JSE3 also decreased the amounts of collagen content accumulated by CCl(4) intoxication. CONCLUSION: These results suggested that the refined extract of J. sinensis may have a potential to be developed as a therapeutic agent to treat hepatic diseases, such as fatty liver and hepatic fibrosis.